A developed HPLC method for the determination of Alogliptin Benzoate and its potential impurities in bulk drug and tablets - Kun Zhang; Panqin Ma; Wenna Jing; Xiangrong Zhang (Elsevier, 2015)
Alogliptin (AGLT), active ingredient of Alogliptin Benzoate (AGLT-BZ), is a new dipeptidyl peptidase-4 (DPP-4) inhibitor for the treatment of type 2 diabetes. This study aimed to build a suitable method to determine the potential related substances in AGLT-BZ bulk drug and tablets. Seven related substances in Alogliptin Benzoate substances were synthetized and identified by 1H-NMR and ESI-MS. In addition, the impurities were detected by a gradient reverse-phase high performance liquid chromatography (RP-HPLC) with UV detection. The chromatographic system consisted of an Angilent Zobax SB-CN column (250 × 4.6 mm; 5 μm). The mobile phase consisted of water/acetonitrile/trifluoroacetic acid 1900:100:1 v/v/v (solution A) and acetonitrile/water/trifluoroacetic acid 1900:100:1 v/v/v (solution B) using a gradient program at a flow rate of 1.0 ml/min with 278 nm detection and an injection volume of 20 μl. Additionally, selectivity, the limit of quantitation (LOQ) and limit of detection (LOD), linearity, accuracy, precision and robustness were determined. Linearity was good over the concentration range 50-1000 ng/ml and the coefficient of determination (R2) were 0.9991-0.9998. RSD% of the determination of precision were <2% (n = 6). The method of RP-HPLC for the determination of impurities in AGLT-BZ was proved to be precise, accurate, robust and reliable. Three batches of self-made bulk drug and three dosages of commercial tablets were detected with this method.